2011
DOI: 10.5054/tj.2011.244400
|View full text |Cite
|
Sign up to set email alerts
|

Reading, Writing, and Learning in ESL: A Resource Book for Teaching K‐12 English Learners (5th Ed.)

Abstract: To further my knowledge of promising practices for teaching reading, writing, listening, and speaking skills to English to speakers of other languages (ESOL) students, I purchased this text.(That was more than 10 years ago.) I found it to be a quick read, user-friendly, and with helpful visuals (graphs, charts, pictures, comics, etc.) that made it engaging and kept my interest.Since then, I have taught the course Instruction and Assessment for English Language Learners to teachers many times and have used this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 0 publications
4
140
0
Order By: Relevance
“…Mikulecky's (1990) and Musumeci's (1997) concept of reading readiness prerequisites is firmly argued by Peregoy & Boyle (2001). According to the latter group, there is adequate evidence which showed that many English speakers and learners are proved to be able to read without any reading readiness prerequisites.…”
Section: Some Perspectives On Reading Theory and Researchmentioning
confidence: 95%
“…Mikulecky's (1990) and Musumeci's (1997) concept of reading readiness prerequisites is firmly argued by Peregoy & Boyle (2001). According to the latter group, there is adequate evidence which showed that many English speakers and learners are proved to be able to read without any reading readiness prerequisites.…”
Section: Some Perspectives On Reading Theory and Researchmentioning
confidence: 95%
“…As Peregoy and Boyle (2012) addressed that as teachers begin to learn more about their students, they will be better able to offer them social and emotional support to meet their needs in their growth Believe all children can succeed, see teaching as "pulling knowledge out" versus putting it in, view knowledge critically, as continually recreated and shared, facilitate fluid teacher-student relationships that are equitable, demonstrate connectedness with all students, encourage students to learn collaboratively, help students develop necessary skills, and seek excellence but take individual differences into account. (as cited in Allington & Johnston, 2002, p. 22) Those shared effective teaching attitudes not only encourage students' motivations to learn, but also enable teachers to modify their teaching strategies in order to effectively and respectfully communicate and interact with students.…”
Section: Teachers' Attitudes and Beliefs Toward Studentsmentioning
confidence: 99%
“…As Peregoy and Boyle (2012) claimed that teachers and students bring to the classroom particular cultural orientations that affect how they perceive and interact with each other in the classroom. While teachers have students whose languages and cultures differ from their own, they need to learn about students and their cultures, while at the same time, reflecting on their own culturally rooted teaching perspectives and behaviors that may facilitate or interfere with teaching and learning (Peregoy & Boyle, 2012). To achieve this goal, teachers need to acquire basic aspects of culture in the classroom as a starting point for reconsidering teaching effectiveness in culturally and linguistically diverse classrooms.…”
Section: Developing Effective Reading Instruction For Multi-cultural mentioning
confidence: 99%
“…According to Vygotsky's zone of proximal development-an important tool for defining scaffolding in learning (Peregoy & Boyle, 2004)-teaching is not focused on today; rather, it emphasizes tomorrow. Students need to be challenged, while receiving assistance and support, to develop to the next level.…”
Section: Learner-centered Design (Lcd)mentioning
confidence: 99%